Protein adhesion on dental surfaces—a combined surface analytical approach - Müller, Christine; Wald, Johanna; Hoth-Hannig, Wiebke; Umanskaya, Natalia; Scholz, Daniel; Hannig, Matthias; Ziegler, Christiane (Analytical and bioanalytical chemistry, 2011)
Protein adsorption is a field of huge interest in a number of application fields. Information on protein adhesion is accessible by a variety of methods. However, the results obtained are significantly influenced by the applied technique. The objective of this work was to understand the role of adhesion forces (obtained by scanning force spectroscopy, SFS) in the process of protein adsorption and desorption. In SFS, the protein is forced to and retracted from the surface, even under unfavorable conditions, in contrast to the natural situation. Furthermore, adhesion forces are correlated with adhesion energies, neglecting the entropic part in the Gibbs enthalpy. In this context, dynamic contact angle (DCA) measurements were performed to identify the potential of this method to complement SFS data. In DCA measurements, the protein diffuses voluntarily to the surface and information on surface coverage and reversibility of adsorption is obtained, including entropic effects (conformational changes and hydrophobic effect). It could be shown that the surface coverage (by DCA) of bovine serum albumin on dental materials correlates well with the adhesion forces (by SFS) if no hydrophobic surface is involved. On those, the entropic hydrophobic effect plays a major role. As a second task, the reversibility of the protein adsorption, i.e., the voluntary desorption as studied by DCA, was compared to the adhesion forces. Here, a correlation between low adhesion forces and good reversibility could be found as long as no covalent bonds were involved. The comparative study of DCA and SFS, thus, leads to a more detailed picture of the complete adsorption/desorption cycle.